THE EFFECTS OF POSTER IN ENHANCING STUDENTS' ABILITY TO WRITE DESCRIPTIVE TEXT USING DIRECT INSTRUCTION MODEL AT THE SECOND GRADE OF JUNIOR HIGH SCHOOL - Ainun Fatikasari; Bahrun Amin; Firman (FKIP Unismuh Makassar, 2022)
This research was studied the effects of poster on students writing of descriptive text using the Direct Instruction Model at the second grade of SMPN 1 Makassar for the 2020/2021 academic year which focused on the use of subject or idol posters. This helps students to understand the material easier and presents an interesting way of the learning process. A pre-experimental research was used with pre-test and post-test in one class by writing text in a paragraphs which took approximately two months period for collecting the data. The research subjects were the eight-grade of student in the C-Class which consisted of nineteen students who took online classes. In this research, the researcher used purposive sampling technique for selecting a sample. The results of this study indicate an enhancement in students writing descriptive text. This is evidenced by the students mean score in the pre-test (45.84) which was lower than the post-test score (82.26). The t-test value was higher than the t-table value (11,880> 1,734). This means that there was a significant difference between the use of posters through the Direct Instruction Model in writing descriptive text which focused on the use of subject or idol poster. Therefore, H0 is rejected and H1 is accepted. Hence, it can be concluded that the poster could enhance students ability in writing descriptive text by using direct instruction model at the second grade of junior high school.